Chest Imaging of a rare case of cat-scratch disease in a 2-years-old baby - Rossi, Enrica; Perrone, Anna; Bongini, Ubaldo; Cangelosi, Antonina Marta; Sollai, Sara; Narese, Donatella; Defilippi, Claudio (Acta Biomedica Atenei Parmensis, 2019)
Cat-scratch disease (CSD) is usually a self-limiting infection that in the majority of cases occurs as lymphadenitis in children who have been scratched or bitten by a cat. Rarely, Bartonella henselae is cause of fever of unknown origin (FUO), with dissemination to various organs, mimicking an inflammatory rather than a lymphoproliferative disease. This manuscript will present a case of thoracic manifestations of CSD in an immunocompetent 2-years baby without history of cat contact, with fever of unknown origin, investigated by chest CT and MRI.